Review on panchatheepakini chooranam - herbal drug for gastrointestinal disorders in Siddha Medicine - Shanthujah, S.; Pancharajah., S.; Prasad, V.M. (University of Jaffna, 2020)
Siddha Medicine is one of the ancient Tamil Medicine. It was originated by Siddhars. All the diseases are caused by imbalance of Thiridhosa (Vatha, Pitha, Kabha). Which depend on intake of food, life style and environmental factors. According to the sage Therayar, the primary cause of disease is “Amam”, which is caused by indigestion. “Pancha theepaakini chooranam” is used to treat “amam”. Therefore authors decided to review “Pancha theepaakini chooranam”. Nine Siddha literatures were selected to collect data for ingredients, parts used, taste, veerya, vipaha, actions, dosage, anupaana and uses. These data were tabulated and analyzed. Same ingredients are used to prepare the “Pancha theepaakini chooranam” and also the parts used are same. Four ingredients (80%) have pungent taste. But black pepper has bitter taste too and long pepperhas sweet taste only. In veerya, 4 (80%) have hot and 1 (20%) has cold. In vipaham, 3 (60%) have pungent and 2 (40%) have sweet.All the ingredients have stimulant and carminative actions. But black pepper has diuretic, acoid, antiperiodic, rubifacient, antivatha, antidote, stomachic actions and cumin has resolvent and astringent actions too.Out of nine books, seven books mentioned the dosage (1-2)g for adults. All these nine books mentioned honey/ghee as anupaana (Vehicle). Ghee has stomachic action and honey makes the medicine palatable. Seven books mentioned the usage of “Pancha theepaakini chooranam”. It is used to cure the abdominal distention, pain, asthisuram, fainting, leucorrhoea and vayu diseases. Agasthiyar vaithiya soothiram stated that the “Pancha theepaakini chooranam” can be used in kabha diseases, maantham, indigestion and vertigo. Siddha maruthuva pettaham stated that it can be used in kabha diseases, maantham, stimulate hunger, indigestion and tasteless sensation. Further study should be carried out to determine the efficacy of “Pancha theepaakini chooranam”.
Keywords: Review; Pancha theepaakini chooranam; Thiridhosas; Siddha Medicine